2021
DOI: 10.3390/antiox10071155
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Patients with Advanced CKD and Renal Replacement Therapy: The Key Role of Peripheral Blood Leukocytes

Abstract: Oxidative stress plays a key role in the pathophysiology of chronic kidney disease (CKD). Most studies have investigated peripheral redox state focus on plasma, but not in different immune cells. Our study analyzed several redox state markers in plasma and isolated peripheral polymorphonuclear (PMNs) and mononuclear (MNs) leukocytes from advanced-CKD patients, also evaluating differences of hemodialysis (HD) and peritoneal dialysis (PD) procedures. Antioxidant (superoxide dismutase (SOD), catalase (CAT), gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…The increased oxidative stress observed in hemodialysis patients could play a significant role in mortality and infectious morbidity, particularly among patients with an elevated malnutrition‐inflammation status. Malnutrition could be aggravated by hemodialysis due to loss of micronutrients during the procedure, dietary restrictions, and enhanced oxidative‐inflammatory stress 39 …”
Section: Discussionmentioning
confidence: 99%
“…The increased oxidative stress observed in hemodialysis patients could play a significant role in mortality and infectious morbidity, particularly among patients with an elevated malnutrition‐inflammation status. Malnutrition could be aggravated by hemodialysis due to loss of micronutrients during the procedure, dietary restrictions, and enhanced oxidative‐inflammatory stress 39 …”
Section: Discussionmentioning
confidence: 99%
“…In general, redox homeostasis is critical for cell viability, activation, proliferation, and organ function [ 36 , 37 ]. Further, the accumulation of ROS is associated with the pathogenesis of CKD [ 38 , 39 , 40 , 41 ] and influences cellular function and mortality in PD patients [ 1 , 42 , 43 , 44 , 45 ]. Our results showing increased oxidative DNA-damage are consistent with previous studies demonstrating increased damage due to attenuated defense mechanisms [ 7 , 46 ] and studies showing that both hemodialysis and peritoneal dialysis induces oxidative DNA-damage in patients or in peritoneal mesothelial cells of PD patients [ 44 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that significantly enhanced oxidative stress and damage in peripheral and mononuclear leukocytes and increased plasma levels of xanthine oxidase, oxidized glutathione (GSSG), and malondialdehyde; decreased superoxide dismutase, catalase, glutathione peroxidase, and glutathione (GSH); and altered GSSG/GSH balance were found in non-dialysis-dependent-CKD, and hemodialysis patients compared to healthy controls ( Vida et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%